(untitled) - Cinar, Ali (New York, 2003)
Offers valuable simulation and control strategies for batch fermentation applications in the food, pharmaceutical, and chemical industries. Enhanced by a corresponding website detailing the latest advances in the field, as well as valuable updates to the material. Provides approaches for determining optimal reference trajectories and operating conditions.
Keywords: Fermentation